The Tīvaevae Methodology and its Application to Palliative Care Research - Henry, Amy (Macmillan Brown Centre for Pacific Studies, 2025)
Health researchers have an ethical responsibility to ensure their research aligns with the health and wellbeing needs, solutions, and aspirations of the communities they study. This ethical responsibility is often heightened in palliative care research. This article reflects on the use of the Tīvaevae methodology – a Cook Islands research methodology – in a study which aimed to understand what palliative care means to Cook Islands families in New Zealand. There is limited research on the needs and understanding of palliative care for Pacific peoples and a near absence of literature that focuses on the needs of Cook Islands peoples in palliative care. More broadly, there is little documented on Cook Islands cultural understandings and knowledge on death, dying, and end-of-life care. As the majority of Cook Islanders reside in New Zealand, and new generations of Cook Islanders in New Zealand find themselves in the position of becoming caregivers to palliative (and often older) family members, understanding what their needs are will be important for families and clinicians alike. In this article, I argue that the Tīvaevae methodology can be used as a guide in the process of contextualising the concept of palliative care to understand palliative care within a Cook Islands context.
Keywords: Tīvaevae; Palliative care; Hospice; Pacific health; Tapu; Noa